Inflammation vs. multiple AVN sites: a nuclear medicine evaluation in systemic allergic-immune syndrome – a case report - Ayan Dhiman; Roshan Karna; Mehul Taggar; Shamim Ahmed Shamim (Annals of Medicine & Surgery, 2026)
Introduction: Migratory polyarthralgia often indicates inflammatory or autoimmune pathology. In patients with concomitant allergic diathesis and immune dysregulation, diagnosis becomes particularly challenging, as conventional laboratory and serological evaluations frequently remain inconclusive. Nuclear medicine, particularly three-phase 99mTc-MDP bone scintigraphy with SPECT/CT, offers functional insights that overcome these limitations by directly visualizing bone metabolic activity, independent of serological status. Case presentation: A 27-year-old woman with bronchial asthma and allergic bronchopulmonary aspergillosis (ABPA) presented with an 11-month history of migratory polyarthralgia. Her background included recurrent anaphylaxis, multiple prior viral infections, and significant systemic corticosteroid exposure (intravenous methylprednisolone 40 mg/day for 10 days, followed by oral methylprednisolone 30 mg three times daily, with subsequent tapering over a total course from September to November 2024), resulting in cushingoid features. Three-phase 99mTc-MDP bone scintigraphy demonstrated increased tracer uptake across multiple joints, consistent with inflammatory arthropathy, and SPECT/CT correlation revealed multifocal avascular necrosis (AVN) and subclinical synovitis in the bilateral femoral heads, elbows, wrists, knees, and ankles. MRI of the right knee and both hips provided anatomical confirmation. Clinical discussion: This case illustrates the diagnostic utility of bone scintigraphy in immune-allergic overlap syndromes in which conventional investigations are inconclusive. SPECT/CT enables the simultaneous delineation of inflammatory and ischemic etiologies, directly guiding therapeutic decision-making, including bisphosphonate therapy and joint-protective rehabilitation. Conclusion: Three-phase 99mTc-MDP bone scintigraphy with SPECT/CT serves as a crucial imaging modality in evaluating complex polyarthralgia. These findings enabled timely therapeutic intervention, including reassessment of corticosteroid use, institution of bisphosphonate therapy (zoledronic acid), and joint-protective rehabilitation, illustrating the direct clinical impact of advanced nuclear medicine imaging. The persistence of symptoms despite treatment highlights the refractory nature of multifocal corticosteroid-induced AVN and the need for continued multidisciplinary follow-up.